Breed‐specific reference ranges for standard echocardiographic measurements in salukis. (31st January 2019) - Giraut, S.; Häggström, J.; Koskinen, L. L. E.; Lohi, H.; Wiberg, M.
Abstract : Objectives: To establish normal reference ranges for standard echocardiographic measurements in Salukis and to examine whether bodyweight, age, gender and heart rate had an influence on the echocardiographic variables. Materials and Methods: Seventy‐five privately owned healthy purebred Salukis, aged 2 to 10 years were included. Case history was obtained and dogs were examined by physical examination, complete blood cell count, serum biochemistry and echocardiography. Associations between bodyweight, gender, sex and heart rate and echocardiographic variables were examined using multiple linear regression analysis and allometric scaling. Reference values with 95% prediction intervals were calculated from regression equations. Results: Bodyweight was a significant predictor of left ventricular diameters, left ventricular volumes and E ‐point‐to‐septal‐separation. Associations between bodyweight and the echocardiographic variables were best described by multiple linear regression models, providing bodyweight‐based reference values. Age, gender and heart rate had significant effect on some of the echocardiographic variables and were included in the final models. When the equation included heart rate or age, reference values were calculated using mean heart rate value (80 bpm) and median age value (73 months). Clinical Significance: This study provides detailed bodyweight‐based echocardiographic values in normal Salukis which can be used as reference values.